Plant Tissue Analysis and Interpretation for Vegetable Crops in Florida - G. J. Hochmuth; E. Hanlon (EDIS)
This guide is provided to assist vegetable growers, UF/IFAS Extension personnel, and consultants in conducting a meaningful plant tissue testing program. Guidelines are provided for collecting samples, proper handling of the sample, and choosing an analytical lab. Information is also presented on basic plant nutrition so that the reader understands the nutrient requirements of each vegetable crop and the process of identifying nutrient deficiencies.